Local wisdom-based teaching materials to improve student problem-solving - Siti Sriyati; Findi Septiani; Kadek Sera Harlistya Udayani; Amprasto Amprasto (Universitas Ahmad Dahlan, 2021)
Improving students' problem-solving skills can be done through teaching materials. Teaching materials used in schools throughout Indonesia have not been integrated with local potential or wisdom. This research aims to develop teaching materials based on local wisdom to improve students' problem-solving abilities. The local wisdom raised in the teaching materials is the local wisdom of agriculture in Binjai Medan and the Balinese environment based on the local wisdom of the Tumpek Wariga ceremony. The development of teaching materials uses the ADDIE design model (Analyze, Design, Develop, Implement, Evaluate). The implementation phase uses a quasi-experimental method with a non-equivalent control group design in a high school located where the local wisdom applies. The results showed that the feasibility test of teaching materials and the readability test showed that teaching materials based on local agricultural wisdom in Binjai were 83.643% (very feasible) and 77.13% (high).Â In contrast, environmental teaching materials in Bali were based on local wisdom Tumpek Wariga. Successively very feasible (88.10%) high (95.39%). Students' problem-solving ability has increased with an N-gain of 0.67 (medium) on teaching materials based on local agricultural wisdom in Binjai and 0.71 (high) in Balinese environmental teaching materials based on Tumpek Wariga. The study results showed that teaching materials based on local wisdom of Agriculture in Binjai and Tumpek Wariga in Bali were valid and could improve students' problem-solving skills on Ecosystem and Environmental Change materials.